Two new species of the codling fish genus Physiculus from Lakshadweep, India (Gadiformes: Moridae) - Babu, K. K. Idrees; Ho, Hsaun-Ching; Mariyambi, P.c.; Sureshkumar, S. (Zootaxa, 2022)
The genus Physiculus is widespread in the Indo-Pacific with more than 32 valid species, and about 12 species were recorded only from the Indian Ocean. Two new species similar to each other are collected from the outer reef drop off of Kavaratti Island, Lakshadweep, India, Arabian Sea and described. Physiculus indicus sp. nov. is characterised by its light organ situated at about the middle of pelvic-fin base and anus, a small light organ, a rather forward situated anus, no scales on the gular region, dorsal-fin rays 8‒9+56‒60, anal-fin rays 55‒60, and 52 vertebrae. This species differs from nearest congeners in lacking gular scales, anus situated closer to the light organ and slightly fewer total vertebrae. Physiculus lakshadeepa sp. nov. is characterised by a relatively high first dorsal fin (51.7‒62.8% HL) and a light organ situated at the middle of the pelvic-fin base and anus. It has a small light organ, a rather forward situated anus, no scales on the gular region, dorsal-fin rays 8‒9+51‒59, anal-fin rays 53‒59, and 49 vertebrae. Physiculus lakshadeepa differs from the nearest congeners in lacking gular scales, fewer anal-fin rays and fewer total vertebrae.